Exploring the Link between Bank Mergers and Credit and Systemic Risk: An Overview - Sunny; Dalal, Garima (International Journal of Social Sciences and Management, 2025)
The banking industry has always been important to the world economy, and is recently facing several challenging issues, so banks should be proactive rather than reactive to the shifting business environment, and the purpose of this paper is to develop insights into how such research is developing and to outline future research opportunities. In this research, a literature evaluation is conducted on the connection between bank mergers and credit risk, and systemic risk. These mergers have resulted in a concentration of resources; yet, they have also led to an increased chance of credit risk and systemic risk as a result of these mergers. It was found that the impact of bank mergers on bank credit and systemic risk is complex and multifaceted. While mergers can lead to increased efficiency and better access to credit, they can also lead to a reduction in lending and increased systemic risk. Int. J. Soc. Sc. Manage. Vol. 12, Issue-4: 185-190.